1991
DOI: 10.1111/j.1744-6570.1991.tb00961.x
|View full text |Cite
|
Sign up to set email alerts
|

PREDICTING TRAINING SUCCESS: NOT MUCH MORE THAN g

Abstract: The roles of general ability (g) and specific abilities (s1…sg) were investigated in prediction of job‐training‐school grades. Subjects were 78,041 Air Force enlistees in 82 jobs. General ability and specific abilities were defined by scores on the first and subsequent unrotated principal components of the enlistment selection and classification test, the Armed Services Vocational Aptitude Battery. Linear models analyses revealed that s1…s9 added little to the prediction afforded by g. It was also determined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
188
2
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(195 citation statements)
references
References 25 publications
3
188
2
2
Order By: Relevance
“…Clark and Voogel (1985) argue that "one of the most common and supportable findings in educational research is that far transfer is achieved by students with higher general ability scores" (p. 120). Ree and Earles (1991) examined which measure of intelligence best predicted training success and found that general intelligence was best. Kanfer and Ackerman (1989) found cognitive ability clearly exerted an effect on trainee performance due to its effect on attentional resource capacity, and Robertson and Downs (1979) found trainee ability accounted for 16% of the variance in training effectiveness.…”
Section: Cognitive Abilitymentioning
confidence: 99%
“…Clark and Voogel (1985) argue that "one of the most common and supportable findings in educational research is that far transfer is achieved by students with higher general ability scores" (p. 120). Ree and Earles (1991) examined which measure of intelligence best predicted training success and found that general intelligence was best. Kanfer and Ackerman (1989) found cognitive ability clearly exerted an effect on trainee performance due to its effect on attentional resource capacity, and Robertson and Downs (1979) found trainee ability accounted for 16% of the variance in training effectiveness.…”
Section: Cognitive Abilitymentioning
confidence: 99%
“…Accordingly, the present study was designed to address a number of individual-level hypotheses. Given that it has been well established that g is a valid predictor of complex skill acquisition and training success (Fleishman & Mumford, 1989;Ree & Earles, 1991) and much of the research on cooperative learning generally suggests that learning is enhanced when individuals are paired with highability partners, we examined the following hypotheses.…”
Section: Ability-based Pairing Strategies and Individual Learningmentioning
confidence: 99%
“…but she was lazy." Natural talent, indexed by IQ score, predicts performance in school and in jobs initially (Hunt, 1995;Ree & Earles, 1991;Schmidt & Hunter, 1998). High performers in professions typically have high IQ scores (Barron & Harrington, 1981).…”
Section: What Is Natural Talent?mentioning
confidence: 99%